Memahami Konsep Kepentingan Diri menurut Agustinus dan Hobbes - Alwino, Alfensius (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2018)
While for Plato, self-interest is a harmonization between reason, emotion, and lust, for Augustine, it is a dark act rooted in self-love. Plato is of the opinion that emotions and passions must be subordinated to reason. Augustine believes that reason, emotion, and lust are to be subjugated to the absolute God since God is the source of harmony. Hobbes dismisses the idea of God as the source of harmony because God is considered as a metaphysical concept that is incomprehensible and cannot be proven empirically. Hobbes’ approach is scientific and empirical. A society should be based not on the idea of God as the source of harmony, but on the power of the leviathan, because in Hobbes’ view the natural state of humans is bellum omnium contra omnes.